2016
DOI: 10.1038/srep26580
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3γ Prevents Centrosome Amplification and Neoplastic Progression

Abstract: More than 80% of malignant tumors show centrosome amplification and clustering. Centrosome amplification results from aberrations in the centrosome duplication cycle, which is strictly coordinated with DNA-replication-cycle. However, the relationship between cell-cycle regulators and centrosome duplicating factors is not well understood. This report demonstrates that 14-3-3γ localizes to the centrosome and 14-3-3γ loss leads to centrosome amplification. Loss of 14-3-3γ results in the phosphorylation of NPM1 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 106 publications
9
44
0
Order By: Relevance
“…This might be an important link between K8 downregulation and increased sensitivity of A431 cells toward apoptotic stimuli. Aside from this, upregulation in 14-3-3c levels and decreased NF-jB activity, further supports this hypothesis [68,69].…”
Section: Discussionsupporting
confidence: 75%
“…This might be an important link between K8 downregulation and increased sensitivity of A431 cells toward apoptotic stimuli. Aside from this, upregulation in 14-3-3c levels and decreased NF-jB activity, further supports this hypothesis [68,69].…”
Section: Discussionsupporting
confidence: 75%
“…Given these observations, we decided to test if D129 and E136 in 14-3-3γ are essential for forming a complex with protein ligands and affecting ligand function. Previous work has demonstrated that 14-3-3γ is found in centrosome fractions (50) and that, loss of 14-3-3γ leads to an increase in centrosome number in human cell lines (24). We wanted to test if mutants of these conserved residues, D129 and E136 in 14-3-3γ, would have any effect on centrosome number.…”
Section: Resultsmentioning
confidence: 99%
“…To test if the effect of the mutants is modulated by the presence of the endogenous protein, we wished to determine the effect of these mutants on centrosome number in the absence of 14-3-3γ as cells with a decrease in 14-3-3γ expression show centrosome amplification (24). We transfected the HCT116 derived vector control or 14-3-3γ knockdown cells with the constructs described above and determined centrosome number in mitotic cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations